Kinerja Pengasuh dalam Pembinaan Akhlak Anak di Panti Asuhan Yatim Piatu Kinderhut Indonesia - Rifqy Masyhur (DAYAH: Journal of Islamic Education, 2018)
Moral is a very important issue in the life of mankind nowadays, especially for children who are still in the growth phase and even more for children who lack attention from their families, such as orphans and broken home children. This is why caregivers in orphanages play a role in fostering the children morals. The purpose of this research was to determine the extent of moral development performed by the caregivers of Kinderhut Indonesia Orphanage in Indrapuri in improving the children's morals. This field research employed qualitative research approach. Data collection was conducted by interview, observation, and documentation. The data were then analyzed by data reduction, data display, and verification to draw conclusions. The respondents of the research consisted of the head of the orphanage, several caregivers and children residing in the orphanage. The results indicated that first, the ability of the caregivers in developing the children’s morals included knowing the nature and characters of the children, communicating well and politely, acting in accordance with religious norms, planning the development program, and being responsible for the children. Second, the coaching methods applied by caregivers were role modeling, habituation, giving advice, storytelling, and promises and punishments. Third, the supporting factors in fostering morals of the children involved a conducive orphanage environment, a religious community environment, and good cooperation between the caregivers and the management of the orphanage. On the other hand, the inhibiting factors were the diverse background of the children and the lack of caregivers. This research is expected to provide benefits to all caregivers in orphanages throughout Indonesia about children's moral development, to the Social Office, to pay more attention to the caregivers in the orphanages, one of which is by providing regular training on the character development of children, and to the universities for sharing knowledge with any caregivers in orphanages and providing enlightenment to them in guiding the morals of children.